2011
DOI: 10.1002/ppul.21522
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography in preterm infants and children with chronic lung disease

Abstract: Summary Objective To determine the utility of overnight polysomnography (PSG) in assessing pulmonary reserve in stable preterm children with chronic lung disease (CLD). Study design: A retrospective review and descriptive study of overnight PSGs and clinic visits of preterm infants/children less than 3 years of age who were diagnosed with bronchopulmonary dysplasia at discharge from the hospital and enrolled in the Johns Hopkins CLD patient registry between 2008 and 2010. Results Sixty-two clinically stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 33 publications
1
43
0
1
Order By: Relevance
“…Using cross‐sectional data we found an association between age and RDI, with improvement in RDI with increasing age, which is consistent with our prior work which did use longitudinal data of a subset of subjects from the same database . Improvement in RDI with age may be due to a maturation in control of breathing, growth of the upper airway, and post‐natal alveolar development resulting in better pulmonary reserve.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using cross‐sectional data we found an association between age and RDI, with improvement in RDI with increasing age, which is consistent with our prior work which did use longitudinal data of a subset of subjects from the same database . Improvement in RDI with age may be due to a maturation in control of breathing, growth of the upper airway, and post‐natal alveolar development resulting in better pulmonary reserve.…”
Section: Discussionsupporting
confidence: 88%
“…There are limited data on the prevalence of SDB in children with a history of BPD. Studies evaluating polysomnograms (PSGs) performed on infants with BPD have found a higher rate of respiratory events compared to non‐BPD infants . During sleep, there is a reduction in airway muscle activity and ventilatory effort.…”
Section: Introductionmentioning
confidence: 99%
“…98 Polysomnography is more sensitive than clinic-based assessments for weaning support and may be useful in determining levels or types of respiratory support and determining optimal timing for weaning off of home ventilation. 104 When polysomnography is not available, alternative approaches, such as pulse oximetry and end tidal CO 2 monitoring, should be considered. In some cases, inpatient observation may be required for ventilator weaning, escalation of support, or capping of tracheostomies for safety purposes.…”
Section: Transitional and Postdischarge Care Of Infants With Sbpdmentioning
confidence: 99%
“…Ideas and suggestions were deliberated, including criteria for establishing home oxygen, weaning regimes and performing polysomnography. All 25 quiz questions were also scored against criteria for abnormal overnight oximetry studies published by the TSANZ (mean SpO 2 < 93–95%), the BTS (mean SpO 2 < 93%), the ATS (≥ 5% of study time with SpO 2 ≤ 93%) and BTS (≥ 5% of study time with SpO 2 ≤ 90%) . Using the consensus answers as a gold standard, sensitivity and specificity were calculated using each criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Although PSG is the gold standard for diagnosing sleep disordered breathing and gas exchange abnormalities, it is not routinely used to guide home oxygen therapy in CNLD because it is expensive, labour intensive and not readily accessible . An alternative is performing overnight oximetry as modern pulse oximeters, calibrated to the lowest averaging time, can accurately monitor continuous arterial oxygen saturations using software algorithms to account for low perfusion and motion artefact .…”
mentioning
confidence: 99%